Communicating to the Public in the Era of Conspiracy Theory. (3rd September 2019) - Connolly, Jennifer M.; Uscinski, Joseph E.; Klofstad, Casey A.; West, Jonathan P.
Abstract : During the last decade, social scientists have taken a strong interest in both the veracity of citizens beliefs and the quality of information on which those beliefs are based. In particular, social scientists have focused much of this work on conspiracy theories given how such theories can undermine government initiatives. The extant literature shows: (1) that the current information environment allows conspiracy theories to spread among citizens farther and faster than ever before; (2) that most Americans believe conspiracy theories; and (3) that conspiracy theories can generate undesirable political and social outcomes. While social scientists have been working to both understand and correct conspiracy beliefs, this literature has yet to inform or to be informed by the relevant scholarship in public administration. This short article attempts to synthesize the conspiracy theory and public administration literatures to make informed recommendations to public administration scholars and public administrators who engage in public outreach during this era of "post-truth."